Protoporphyrin IX loaded polysilsesquioxane nanoparticles: photostability and cellular response to photodynamic therapy - Ilaiáli Souza Leite; Zachary Lyles; Edgar Aparecido Sanches; Vanderlei Salvador Bagnato; Juan Luis Vivero-Escoto; Natalia Mayumi Inada (Photodiagnosis and Photodynamic Therapy, 2025)
Photodynamic therapy (PDT) is a non-invasive therapeutic approach used for the treatment of cancer. Several nanoparticulate systems have been currently developed to enhance the phototherapeutic effect associated with PDT. In particular, polysilsesquioxane (PSilQ) nanoparticles are a promising hybrid platform with numerous advantages to be used as a delivery system. PSilQ nanoparticles were prepared to efficiently carry protoporphyrin IX (PpIX) as a PS agent to treat triplet-negative breast cancer. In this report, the photostability performance of this PSilQ platform was evaluated, as well as its PDT effect on breast cancer (MCF-7) and human dermal fibroblasts, neonatal (HDFn) cell lines. The fluorescence life-time results demonstrated that the PpIX molecules are aggregated inside the PSilQ framework. Nevertheless, similar PDT outcome was obtained against MCF-7 cells as compared to PpIX molecules. Moreover, the PSilQ platform reduced the dark toxicity associated with PpIX in HDFn cells. These relevant features make PSilQ nanoparticles an interesting platform for PDT of cancer.